Penatalaksanaan Fisioterapi Pada Kasus Osteoarthritis Genu Sinistra di RSUD DR. Moewardi Surakarta - , Khairunnisa, Dwi Kurniawati SSt.Ft, M.Kes (2016)
Background: Osteoarthritis (OA) is a degeneration disorder of cartilaginous structure in the joints. The most common joint that have OA is knee. In this case the patient could treated with physiotherapy modalities which are infrared, transcutaneous electrical nerve stimulation and exercise therapy. In this case, physiotherapy could reduce pain, enhance muscle strength and functional activity. Aim of Research: To find out the effect of infra red, transcutaneous electrical nerve stimulation and exercise therapy on pain reduction, enhance muscle strength and functional activity. Result: After sixth therapies, the researcher found there are reduction of quite pain T0:1 to T6 is 1, tenderness T0: 3 to T6: 1, painful motion T0: 1 to T6: 1, to enhance muscle strength of extensor genu T0: 4- T6: 4, flexor genu T0: 4 T6: 4. To enhance functional activity T0: 7,5 T6: 5. Conclusion: Infra red, transcutaneus electrical nerve stimulation and exercise therapy can reduce pain, enhance muscle strength and functional activity.